The role of trust in global health research collaborations - Kerasidou, Angeliki (Bioethics, 2018)
Collaborations in global health research are on the rise because they enhance productivity, facilitate capacity building, accelerate output and make tackling big, multifactorial research questions possible. In this paper, I examine the concepts of trust and reliance in scientific collaborations in general, but also in the particular context of collaborations in global health research between high‐income countries and low‐and‐middle income countries (LMIC). I propose and defend the argument that given the particular characteristics of collaborations and demands of trust relationships, reliance is a better relational mode for successful collaborations. Although reliance can be difficult to establish in situations where asymmetry of power exists, trust should not be the only relational mode available to LMIC researchers because of the type of vulnerability it introduces to the relationship. I conclude that the promotion of good collaborations requires addressing the power imbalances between partners, and establishing an even playing field in global health research.